EURISCO: The European search catalogue for plant genetic resources. Issue Volume 45:Issue D1(2017) (31st August 2016) - Weise, Stephan; Oppermann, Markus; Maggioni, Lorenzo; van Hintum, Theo; Knüpffer, Helmut
Abstract: The European Search Catalogue for Plant Genetic Resources, EURISCO, provides information about 1.8 million crop plant accessions preserved by almost 400 institutes in Europe and beyond. EURISCO is being maintained on behalf of the European Cooperative Programme for Plant Genetic Resources. It is based on a network of National Inventories of 43 member countries and represents an important effort for the preservation of world's agrobiological diversity by providing information about the large genetic diversity kept by the collaborating collections. Moreover, EURISCO also assists its member countries in fulfilling legal obligations and commitments, e.g. with respect to the International Treaty on Plant Genetic Resources, the Second Global Plan of Action for Plant Genetic Resources for Food and Agriculture of the United Nation's Food and Agriculture Organization, or the Convention on Biological Diversity. EURISCO is accessible at http://eurisco.ecpgr.org .